Efektifitas Pelatihan Perawatan Luka Tingkat Dasar di Bapelkes Batam dalam Meningkatkan Kemampuan Tenaga Keperawatan di Provinsi Kepulauan Riau - Wilda Hayati; Endan Suwandana (FORUM ILMIAH KESEHATAN, 2019)
The improvement of wound care capability of nurses needs to be continually conducted due to the development in science and technology of the wound care. One way to improve the capability of the nurse can be achieved by conducting a training program. This paper is aimed to assess the effectiveness of the basic level wound care training program at Health Training Center (Bapelkes) of Batam in the improvement of the nurses’ capabilities in the Kepulauan Riau Province. This study implements qualitative descriptive method by using questionnaires as research instrument which were distributed to three groups of respondents, i.e. the alumni, the alumni’s mentors, and the alumni’s working partners, out of three training batches between 2011-2013. The variables evaluated in this study include performance, working motivation, professional competency, and training competency. The results of the study show that the training program is effective in improving the nurses’ capability in all evaluated variables with the average improvement percentage of 96,88% (based on response of the alumni), 90,63% (based on the response of the alumni’s mentors), and 92,19% (based on the response of the alumni’s working partners). The study also concludes that the correlation of responses among the group of respondents showing that the correlation of the responses between the alumni and the alumni’s mentors is strongly significant with the coefficient correlation (R2) of 0.804 and strong with the R2 of 0,516 for the correlation of the responses between the alumni and the alumni’s working partners. Keywords: post-training evaluation; wound care; nurse ABSTRAK Peningkatan kemampuan perawatan luka perlu terus dilakukan terhadap tenaga keperawatan mengingat ilmu pengetahuan dan teknologi tentang perawatan luka terus mengalami perkembangan. Salah satu upaya untuk meningkatkan kemampuan tenaga keparawatan tersebut adalah melalui kegiatan pelatihan. Tulisan ini bertujuan untuk mengkaji efektifitas pelatihan perawatan luka tingkat dasar dalam meningkatkan kemampuan tenaga keperawatan se-Kepulauan Riau yang dilaksanakan di Balai Pelatihan Kesehatan (Bapelkes) Batam. Penelitian ini menggunakan metode dekriptif kualitatif dengan teknik kuesioner yang diujikan kepada tiga kelompok responden, yaitu alumni, atasan alumni, dan rekan kerja alumni dari tiga angkatan pelatihan yang dilaksanakan pada tahun 2011 – 2013. Variable yang diujikan mencakup unsur kinerja, motivasi kerja, kompetensi profesionalisme, dan kompetensi pelatihan. Hasil kajian ini menunjukkan bahwa pelatihan ini cukup efektif untuk meningkatkan kemampuan alumni pada seluruh variable yang diujikan dengan rata-rata persentase peningkatan sebesar 96,88% (menurut alumni), 90,63% (menurut atasan), dan 92,19% (menurut rekan kerja). Dilihat dari sisi kesesuaian jawaban yang diberikan oleh antar kelompok responden, kajian ini menunjukkan korelasi yang sangat signifikan dengan koefisien korelasi (R2) = 0,804 untuk korelasi antara jawaban alumni dan atasan alumni serta signifikan dengan R2 = 0,516 untuk korelasi antara jawaban alumni dan rekan kerja alumni. Kata kunci: evaluasi pasca pelatihan; perawatan luka; perawat